Multimodal assessment of sleep in men and women during treatment for opioid use disorder. (1st February 2020) - Finan, Patrick H.; Mun, Chung Jung; Epstein, David H.; Kowalczyk, William J.; Phillips, Karran A.; Agage, Daniel; Smith, Michael T.; Preston, Kenzie L.
Highlights: Patients treated with buprenorphine versus methadone did not differ on sleep. EEG revealed shorter and more disrupted sleep than patients self-reported. Sex differences were observed; men had shorter and less deep sleep than women. Abstract: Background: Sleep disturbance is common in patients with opioid use disorder (OUD) receiving medication for addiction treatment. Differences between patients on the two primary agonist medications—methadone and buprenorphine—are not well understood. Methods: In patients receiving either methadone or buprenorphine treatment for OUD, we examined sleep continuity and architecture using ambulatory monitoring to gather both an objective measure (daily sleep EEG; M = 5.76 days, SD = 1.46) and a subjective measure (daily sleep diary; M = 54.10 days, SD = 25.10) of sleep. Results: Patients treated with buprenorphine versus methadone did not differ on any measure of sleep continuity or architecture. Women had longer EEG-derived total sleep time than men (d = -0.68, 95 % CI -1.32 to -0.09), along with lower %N2 (d = 0.94, 95 % CI 0.34–1.64) and greater %N3 (d = -0.94, 95 % CI -1.61 to -0.32). Self-reported sleep differed from EEG-derived estimates: wake after sleep onset was greater by EEG than by diary (d = 2.58, 95 % CI 1.74–3.63), and total sleep time and sleep efficiency were lower by EEG than by diary (d for sleep time = 2.93, 95 % CI 2.06–4.14; d for efficiency = 1.69, 95 % CI 0.98–2.49). Conclusions: Patients treated with buprenorphine or methadone did not substantively differ in ambulatory measures of sleep. With both medications, there was a discrepancy between objective and subjective sleep measures. Further confirmatory evidence would inform the development of sleep-related recommendations for OUD patients undergoing agonist treatment.